A conceptual model for software ecosystem governance. (18th November 2020) - Oliveira, Joyce Aline; Alves, Carina; Valença, George
In a software ecosystem, organisations work collaboratively to survive market changes. To ensure the healthy growth of software ecosystems, governance is essential because it defines suitable strategies and processes to manage relationships in the software ecosystem. Software ecosystem governance is all process by which an actor creates value, coordinates relationships and defines control. Understanding the elements and relationships involved in the software ecosystem governance supports companies to discover which elements act as enabler or barrier to the health of the ecosystem. We proposed a conceptual model to govern software ecosystems. The model was built using design science research and was evaluated through an expert survey and interviews with practitioners. The model increases the theoretical body of knowledge in the field and practitioners can apply it to create governance strategies to foster the healthy evolution of the ecosystem.